Facilitators and Barriers to Implementing the 4Ms Framework of Age-Friendly Health Systems: A Scoping Review - Huey-Ming Tzeng; Hannah E. Franks; Elise Passy (MDPI AG, 2024)
Background: This scoping review explored the evidence in the peer-reviewed published journal literature to identify the facilitators and barriers to implementing the 4Ms Framework of Age-Friendly Health Systems in inpatient and outpatient clinical settings. Methods: Our search strategy focused on primary and secondary data sources that described the barriers and facilitators of incorporating the 4Ms Framework in clinical settings. We focused on older adults 65 years and older and followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-SCR). Results: The evidence analyses of the 19 identified articles revealed six facilitator themes and five barrier themes to implementing the 4Ms Framework of Age-Friendly Health Systems in inpatient and outpatient clinical settings. The most recurring facilitator theme was embedding the 4Ms Framework into routine clinical practice with clinical pathways and designated personnel. The most frequently reported barrier theme was the lack of clinicians' buy-in. Conclusions: Future research may translate the findings of this scoping review into a facilitator and barrier checklist or a "reality-check" measure to monitor the progress of the journey of embracing the 4Ms Framework in outpatient or inpatient clinical settings. This study was not registered.